Theory of the Absolute in recentivism and Eastern philosophy - Bańka, Józef (Folia Philosophica, 2009)
The aim of the paper is to make a comparison between two concepts of the Absolute: the one presented in recentivism and the one typical of Eastern philosophy. In the framework of the former the Absolute is conceived of as the Transcendental Recens (The Eternal Present), while in the latter as the most fundamental element, which also exists “now”, but also in us (tat twam asi) and still wanders. In both recentivism and Eastern philosophy the Absolute is present in the universe just as the author in his work; is - silent, but every expression is derived from Him. In both conceptions the Absolute is freed from the burden of the word, as it is given in the concentration of silence, in a metaphysical miracle of the way towards mystery. A fear of what is covered by the mist of the distant premonition is a fear of the experience of the other side of the Absolute.